A Study of Talar Neck in Detail by Comparing the X-Ray Foot Oblique View with Canale and Kelly View - Jayaiswarya, Jayaiswarya; Vayshak, Vayshak; Surendhar, Surendhar; Kumar, Tharun (Journal of Neonatal Surgery, 2025)
Background: Medical imaging plays a vital role in providing images of the soft tissue and internal structures of the body. It uses different modalities for diagnosis and treatment in healthcare for all age groups. For initial diagnostic accuracy, x-rays are instrumental in identifying and assessing fractures, helping clinicians determine the type and severity of the injury. Imaging of the talar neck was quite difficult to interpret in routine foot projections. Method: It is a cross-sectional study with a sample of 50 patients was included. The inclusion criteria were patients with long-term foot pain, walking difficulty, ATFL, osteoarthritis, road traffic accidents, ortho implants and exclusion criteria were patients with no complaints of foot injury, pregnant women. Result: In this study we evaluated 50 patients, the addition of Canale and Kelly’s view radiographs can improve the efficacy of talar neck identification as well as alter clinical treatment plans. Our data demonstrates a trend toward increased accuracy of talar neck identification with the addition of Canale and Kelly’s view radiographs. Conclusion: It is evident that the Canale and Kelly’s view is necessary to obtain a correct view of the talar neck and to correctly identify fractures. It provides a clear visualization of the talar neck and will reveal any neck displacement or malreduction..